2021
DOI: 10.1101/2021.02.02.21250897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on anxiety and depression symptoms of young people in the Global South: evidence from a four-country cohort study

Abstract: Objective To provide evidence on the effect of the COVID-19 pandemic on the mental health of adolescents and young adults who grew up in poverty in Low and Middle Income Countries (LMICs). Design A phone survey implemented August-October 2020 to participants of a population-based cohort study since 2002 comprising two cohorts born in 1994-5 and 2001-2 in Ethiopia, India (Andhra Pradesh and Telangana), Peru and Vietnam. We examined associations between mental health and pandemic-related stressors, as well as s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Economic hardship in terms of job and income loss during COVID-19 has reached a new global high. This has resulted in deteriorating mental health in both high- and low-income countries ( Porter, Favara, Hittmeyer, et al, 2021 ; Salameh et al, 2020 ; Witteveen & Velthorst, 2020 ). While a global issue, research from different platforms has warned that young women in vulnerable communities in the developing world are at a greater risk of suffering from anxiety and mental stress due to rising financial hardship ( Plan International, 2020 ; UN, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Economic hardship in terms of job and income loss during COVID-19 has reached a new global high. This has resulted in deteriorating mental health in both high- and low-income countries ( Porter, Favara, Hittmeyer, et al, 2021 ; Salameh et al, 2020 ; Witteveen & Velthorst, 2020 ). While a global issue, research from different platforms has warned that young women in vulnerable communities in the developing world are at a greater risk of suffering from anxiety and mental stress due to rising financial hardship ( Plan International, 2020 ; UN, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to such findings, this study found no significant gender effects, though overall percentages of symptomatic women were slightly more than that of men across mild (M = 17%, F = 18%), moderate (M = 16%, F = 18%), and severe (M = 16%, F = 17%) categories. In their study comparing depression among the youth of Peru, Ethiopia, Vietnam, and India during the pandemic, Porter et al ( 2021 ) found similar results in Indian youth. One reason for variations observed in studies conducted during the pandemic could be the stress-inducing conditions imposed by the pandemic regardless of gender.…”
Section: Discussionmentioning
confidence: 89%
“…Fluctuations in perception of the pandemic over time as being less dangerous (data collection took place in November when the first wave was coming to an end) may contribute to lower emotional impact (Terry et al, 2020 ). Several external and intrinsic factors moderate COVID-related depression in young people and a clearer understanding of the experience of depression during the pandemic requires an inquiry into these factors (Porter et al, 2021 ; Rehman et al, 2021 ; Sundarasen et al, 2020 ; Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on pre-pandemic research, 20 we highlight the association between food shortages and continuing high rates of poor mental health. Young Lives research shows food insecurity increased during the pandemic, except in Vietnam 1 and that pandemic-related stressors worsened mental health in mid-2020 21 . A 149-country pre-pandemic study 20 found that food insecurity is associated with poorer mental health and identifies channels through which food insecurity affects mental health: i) feelings of powerlessness, sadness, frustration ii) uncertainty regarding acquiring sufficient food iii) feelings of guilt/shame from acquiring food in socially unacceptable ways.…”
Section: Discussionmentioning
confidence: 99%